DETERMINANTS OF CONSUMER DECISION IN SELECTING BEAUTY PARLOR AND SALON IN MANADO (Case Study of St Laurent Beauty Parlor and Salon in Manado) - Tooy, Novrico .; Lapian, S.L.H.V. Joyce (Universitas Sam Ratulangi, 2018)
Abstract: Physical Beauty is an advantage as being beautiful gives a person much more confidence it is also become a significant importance at personal, social and professional level. St Laurent Beauty Parlor and Salon is popular place for people in Manado to get beauty treatments at. This research aims to identify the determinants of consumer decision in selecting beauty parlors and salons in Manado with the study case being St. Laurent Beauty Parlor and Salon. Knowing these determinants, marketers can better understand them using them to their advantage to gain more customers. In order to define these determinants this research takes a quantitative approach by obtaining data through questionnaires using convenience sampling in which 100 customers of St. Laurent Beauty Parlor and Salon are the respondents. To analyze the data this research uses Factor Analysis as the research method. There are 20 variables included in the analysis, and the results show that all 20 variables correlate with the other factors. From the results of the factoring process there are 3 factors formed which are: Customer Satisfaction, Customer Relationship and Promotion. St Laurent Beauty Parlor and Salon should have the presence of a pleasant aroma around the salon because it has positive effects on consumers. Customers will want to stay longer in a good smelling store and the stimulating fragrance makes them comfortable with this place.Â Keywords: st. laurent beauty parlor and salon, consumer decision, factor analysisÂ